2006
DOI: 10.1111/j.1432-2277.2006.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary cytotoxic molecular markers for a noninvasive diagnosis in acute renal transplant rejection*

Abstract: Summary Perforin (P), Granzyme B (GB) and Fas‐Ligand (FAS‐L) are cytotoxic molecules involved in acute rejection (AR) after renal transplantation. A noninvasive diagnostic test to monitor AR and other complications could improve clinical management. We investigated the predictive and diagnostic interest of target mRNA measurements, with a quantitative PCR assay, in AR, as well as in other clinical complications recurrent in kidney transplantation. One hundred and sixty‐two urine specimens from 37 allograft rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 43 publications
5
42
0
1
Order By: Relevance
“…Numerous studies have reported elevated GrB levels in the plasma and inflammatory infiltrate of biopsies from patients experiencing acute rejection, suggesting GrB may be a useful biomarker for the prediction of acute rejection. [237][238][239][240][241][242][243][244][245] Although acute rejection constitutes a major challenge in the early postoperative period, the major impediment to longterm survival for solid organ transplant recipients is allograft vasculopathy (AV), which is an accelerated, immune-mediated form of occlusive arteriosclerotic vascular disease that affects vessels of solid organ allografts. 307,308 The pathogenesis of AV is complex and characterized by intimal accumulation of SMCs, T lymphocytes, and macrophages, as well as extensive medial thinning that is associated with increased SMC apoptosis.…”
Section: Cardiac Allograft Vasculopathymentioning
confidence: 99%
“…Numerous studies have reported elevated GrB levels in the plasma and inflammatory infiltrate of biopsies from patients experiencing acute rejection, suggesting GrB may be a useful biomarker for the prediction of acute rejection. [237][238][239][240][241][242][243][244][245] Although acute rejection constitutes a major challenge in the early postoperative period, the major impediment to longterm survival for solid organ transplant recipients is allograft vasculopathy (AV), which is an accelerated, immune-mediated form of occlusive arteriosclerotic vascular disease that affects vessels of solid organ allografts. 307,308 The pathogenesis of AV is complex and characterized by intimal accumulation of SMCs, T lymphocytes, and macrophages, as well as extensive medial thinning that is associated with increased SMC apoptosis.…”
Section: Cardiac Allograft Vasculopathymentioning
confidence: 99%
“…In addition, our study suggested that FOXP3 may be superior to conventional rejection markers, such as perforin, Fas-L and IP-10, in terms of detecting early rejection. [44][45][46][47] The possibility of FOXP3 being a marker for an early phase of rejection was supported by our finding that a rescue immunosuppressive therapy, which was started when peak FOXP3 level was noted, significantly prolonged graft survival, but not in a therapy started when rejection was suspected by chest radiography. However, because the expression of FOXP3 was upregulated only early post-transplantation, a combination of FOXP3 and chest radiography may detect rejection more efficiently than FOXP3 alone or chest radiography alone.…”
Section: Discussionmentioning
confidence: 57%
“…Recently Li et al (11) reported that mRNA levels of T cell-related cytotoxicity molecules perforin and granzyme B were enhanced in urine samples from AR patients. Other groups showed similar results (30)(31)(32). However, the role of the measurement of mRNA in urine samples as indicators of graft function at different times post-KT is less clear.…”
Section: Discussionmentioning
confidence: 70%